Empowering communities: Education for hypertension and diabetes prevention - Ratih Wirapuspita Wisnuwardani; Ayudhia Rachmawati; Akhmad Dzikri; Ika Wulan Sari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Hypertension and diabetes serve as significant risk factors for cardiovascular disease. Nutrition education plays a pivotal role in both preventing and managing these conditions. By promoting healthy eating behaviors and encouraging regular exercise, nutrition education can significantly reduce the likelihood of developing these chronic diseases and enhance overall health outcomes. The volunteering project's primary objective is to enhance knowledge about hypertension and diabetes to prevent and manage these conditions in Sepaku, Penajam Paser Utara, East Kalimantan, while also understanding the underlying causes of hypertension and diabetes. Implementation involves conducting lectures utilizing PowerPoint presentations, facilitating discussions, and conducting measurements of glucose levels, blood pressure, weight, and height. Before and after nutrition education, measurements of knowledge about hypertension and diabetes were conducted, with paired t-test analysis. The result of the activity is that participants gained significant information and increased their knowledge about the causes, prevention and treatment of hypertension and diabetes. Therefore, the importance of regular activities in increasing awareness in the prevention and treatment of hypertension and diabetes.